2021
DOI: 10.3390/ijerph18010324
|View full text |Cite
|
Sign up to set email alerts
|

Living with Family Is Directly Associated with Regular Dental Checkup and Indirectly Associated with Gingival Status among Japanese University Students: A 3-Year Cohort Study

Abstract: Although some studies showed that lifestyle was associated with oral health behavior, few studies investigated the association between household type and oral health behavior. The aim of this prospective cohort study was to investigate the association between household type, oral health behavior, and periodontal status among Japanese university students. Data were obtained from 377 students who received oral examinations and self-questionnaires in 2016 and 2019. We assessed periodontal status using the percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…Oral health status (DMFT, %BOP, and OHI-S) was not associated with willingness to undergo regular dental check-ups. Oral health status in the present study was better overall than in recent studies of university students (DMF 0.02 vs. 1.6, %BOP 16.7% vs. 35.5%, and OHI-S 0.2 vs. 0.5) [ 3 , 41 ]. The participants might have been more interested in oral health and had good oral health behaviors.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Oral health status (DMFT, %BOP, and OHI-S) was not associated with willingness to undergo regular dental check-ups. Oral health status in the present study was better overall than in recent studies of university students (DMF 0.02 vs. 1.6, %BOP 16.7% vs. 35.5%, and OHI-S 0.2 vs. 0.5) [ 3 , 41 ]. The participants might have been more interested in oral health and had good oral health behaviors.…”
Section: Discussioncontrasting
confidence: 83%
“…Undergoing regular dental check-ups is significantly associated with good oral hygiene status in Japanese university students [ 1 , 2 ]. However, the percentage of Japanese students undergoing regular dental check-ups is 12.3–30.2% [ 1 , 2 , 3 ], lower than the general Japanese population according to the National Health and Nutrition Survey in 2016 (52.9%) [ 4 ]. On the other hand, in Japan, an oral examination once a year is mandatory for students until the high school period.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can easily change their health and lifestyle behaviors [ 1 , 9 ]. University students’ household type was directly associated with regular dental check-ups and indirectly contributed to gingival status [ 23 ]. Some previous studies reported that oral health behaviors such as tooth brushing, use of dental floss, and regular dental check-ups affected oral hygiene and periodontal status in university students and adults [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, it was observed that nearly half of the participants who lived alone had a history of PD, and living status showed a significant association with the likelihood of PD. Living status is recognized as a strong factor influencing individuals’ oral health [ 24 ]. Living alone is associated with a higher likelihood of developing depressive symptoms compared to living with family members [ 25 ].…”
Section: Discussionmentioning
confidence: 99%